Progress of laser surface treatment on magnesium alloy - Zhang, Shiliang; Jiang, Jing; Zou, Xianrui; Liu, Ning; Wang, Hongshui; Yang, Lei; Zhou, Huan; Liang, Chunyong (Frontiers in Chemistry, 2022)
Magnesium (Mg) metals have been widely used in various fields as one of the most promising lightweight structural materials. However, the low corrosion resistance and poor mechanical properties restrict its applications. Surface treatments are common approach to enhance the mechanical strength and corrosion resistance of Mg metals. Among them, laser surface treatment generates novel tissues and structures in situ on the sample surface, thereby improving properties of mechanical strength and corrosion resistance. We briefly describe the changes in surface organization that arise after laser treatment of Mg surfaces, as well as the creation of structures such as streaks, particles, holes, craters, etc., and provide an overview of the reasons for the alterations. The effect of laser processing on wettability, hardness, friction wear, degradation, biocompatibility and mechanical properties were reviewed. At last, the limitations and development trend of laser treatment on Mg metals research were further pointed out.